THE RELATIONSHIP BETWEEN ALTITUDES AND THE CONTENTS OF PROTEIN, CARBOHYDRATES, LIPIDS OF PUMPKIN (Cucurbita moschata) - Tjiptowibisono, Suranto; Tedianto, Tedianto; Purwanto, Edi; Sety, Prabang (AGRIVITA, Journal of Agricultural Science, 2015)
Cucurbita moschata or pumpkin can be used as an alternative food mainly due to its carbohydrate content, and it is very easy to grow in many different habitats. The objective of this research was to evaluate the biochemical contents of C. moschata based on the altitudes and also to examine whether any relationship between the environmental conditions and protein, carbohydrate and lipid contents. Proximate analysis was used for statistical consideration of the results obtained. Chemical analysis was conducted by using mesocarp of pumpkin after cleaning, peeling and removing seeds from the center of fruits. Kjedahl and soxhlet methods were used to look at the content of protein and lipid respectively. Meanwhile, the method of difference was employed to measure the percentage of carbohydrates. Although there was no significant relationship between the biochemical contents and the environmental conditions, it was recorded that plants grown at higher altitudes with high soil pH and air temperature tended to have higher protein, carbohydrate and lipid contents, compared to that of higher soil moisture. This results showed that the highest biochemical contents of protein, carbohydrate and lipid of two varieties C. moschata were evident at the lowest altitude.Keywords: altitudes, carbohydrates, Cucurbita moschata, lipids, protein